Lean mass, muscle strength, and physical function in a diverse population of men: a population-based cross-sectional study - Araujo Andre B; Chiu Gretchen R; Kupelian Varant; Hall Susan A; Williams Rachel E; Clark Richard V; McKinlay John B (BMC, 2010)
Abstract Background Age-related declines in lean body mass appear to be more rapid in men than in women but our understanding of muscle mass and function among different subgroups of men and their changes with age is quite limited. The objective of this analysis is to examine racial/ethnic differences and racial/ethnic group-specific cross-sectional age differences in measures of muscle mass, muscle strength, and physical function among men. Methods Data were obtained from the Boston Area Community Health/Bone (BACH/Bone) Survey, a population-based, cross-sectional, observational survey. Subjects included 1,157 black, Hispanic, and white randomly-selected Boston men ages 30-79 y. Lean mass was assessed by dual-energy x-ray absorptiometry. Upper extremity (grip) strength was assessed with a hand dynamometer and lower extremity physical function was derived from walk and chair stand tests. Upper extremity strength and lower extremity physical function were also indexed by lean mass and lean mass was indexed by the square of height. Results Mean age of the sample was 47.5 y. Substantial cross-sectional age differences in grip strength and physical function were consistent across race/ethnicity. Racial/ethnic differences, with and without adjustment for covariates, were evident in all outcomes except grip strength. Racial differences in lean mass did not translate into parallel differences in physical function. For instance, multivariate modeling (with adjustments for age, height, fat mass, self-rated health and physical activity) indicated that whereas total body lean mass was 2.43 kg (approximately 5%) higher in black compared with white men, black men had a physical function score that was approximately 20% lower than white men. Conclusions In spite of lower levels of lean mass, the higher levels of physical function observed among white compared with non-white men in this study appear to be broadly consistent with known racial/ethnic differences in outcomes.